2018
DOI: 10.1007/s10147-018-1314-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the University of Pittsburgh staging system and the eighth edition of the American Joint Committee on Cancer TNM classification for the prognostic evaluation of external auditory canal cancer

Abstract: The University of Pittsburgh staging system for patients with EAC cancer is a valuable tool for use in clinical decision-making and predicting survival outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Studies have reported regional metastasis rates of 2.4–12% [10, 11]. The Pittsburgh staging system, originally developed for SCC, has been adopted for EAC carcinoma to attempt to establish staging guidelines, as there is no consensus among staging systems [10, 12]. Recent studies have shown that the University of Pittsburgh staging system carries higher prognostic accuracy than the latest AJCC staging system, with Pittsburgh T classification being an independent predictor of the overall survival rate, thus verifying that the system carries prognostic importance [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have reported regional metastasis rates of 2.4–12% [10, 11]. The Pittsburgh staging system, originally developed for SCC, has been adopted for EAC carcinoma to attempt to establish staging guidelines, as there is no consensus among staging systems [10, 12]. Recent studies have shown that the University of Pittsburgh staging system carries higher prognostic accuracy than the latest AJCC staging system, with Pittsburgh T classification being an independent predictor of the overall survival rate, thus verifying that the system carries prognostic importance [12].…”
Section: Discussionmentioning
confidence: 99%
“…The Pittsburgh staging system, originally developed for SCC, has been adopted for EAC carcinoma to attempt to establish staging guidelines, as there is no consensus among staging systems [10, 12]. Recent studies have shown that the University of Pittsburgh staging system carries higher prognostic accuracy than the latest AJCC staging system, with Pittsburgh T classification being an independent predictor of the overall survival rate, thus verifying that the system carries prognostic importance [12]. The current patient was staged T1N0M0 based on the Pittsburgh system, thus wide local excision was sufficient, as it was a T1 tumor limited to the EAC showing clear margins by histopathology upon removal, without bony erosion or soft-tissue extension [10, 13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low occurrence of temporal bone SCC (TB-SCC) has limited the amount of available data from both clinical and basic research. The Pittsburgh classification system is a globally popular staging system for TB-SCC, especially for the external auditory canal (EAC) carcinoma (1,2). However, this scheme may not accurately reflect tumor extension and lumps resectable and unresectable tumors in the same category: T4.…”
Section: Introductionmentioning
confidence: 99%